Relevance Of Partnership Principles In Company Law: Winding-Up On The ‘Just And Equitable Ground’ - Salim, Mohd Rizal (Journal of Malaysian and Comparative Law, 2001)
Three interesting cases were reported in consecutive years in relation to application by shareholders to wind-up company based on the 'just and equitable' ground pursuant to s 218(1)(i) of the Companies Act 1965. They are Fairview Schools Bhd v Indrani a/p Rajaratnam (No 2), Ngan Tuck Seng v Ngan Yin Hoi and Loh Eng Leong v Lo Mu Sen & Sons Sdn Bhd.